2019
DOI: 10.1097/md.0000000000016535
|View full text |Cite
|
Sign up to set email alerts
|

Nonviral infection-related lymphocytopenia for the prediction of adult sepsis and its persistence indicates a higher mortality

et al.

Abstract: Sepsis is a life-threatening disease that affects 30 million people worldwide each year. Despite the rapid advances in medical technology and organ support systems, it is still difficult to reduce the mortality rate. Early and rapid diagnosis is crucial to improve the treatment outcome. The aim of this study was to investigate the prediction efficiency of lymphopenia and other clinical markers, such as white blood cell (WBC), neutrophil count (N#), procalcitonin (PCT), and arterial lactic acid (Lac) in the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…This is consistent with the rapid development of a hamster model similar to human leptospirosis, which directly leads to severe liver and kidney dysfunction [ 37 , 38 ]. A large number of leptospires could be detected in the blood, and haematological analysis found that the percentage of neutrophils increased and the percentage of lymphocytes decreased, which was a manifestation of severe sepsis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the rapid development of a hamster model similar to human leptospirosis, which directly leads to severe liver and kidney dysfunction [ 37 , 38 ]. A large number of leptospires could be detected in the blood, and haematological analysis found that the percentage of neutrophils increased and the percentage of lymphocytes decreased, which was a manifestation of severe sepsis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALCs usually decrease to similar levels in survivors and non-survivors in the early stages of sepsis; however, it experiences lymphocyte recovery in survivors, while that of non-survivors remains low [21]. Previous studies showed that lymphopenia is effective for the early diagnosis of sepsis and indicates a higher mortality [22]. Additionally, ALCs after esophagectomy decreased more than that after colorectal cancer surgery, whilst lymphopenia did not occur after minor surgical procedures [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…A major feature of immunosuppression in sepsis is immune cell apoptosis, similar to the decreased levels of circulating lymphocytes 6 . Apoptosis, autophagy and other factors contribute to the early reduction in lymphocyte count [6][7][8] . In addition, procoagulant dysfunction is another important feature of sepsis, and many studies have revealed a close relationship between the infectious inflammatory response and coagulation function [9][10][11][12] .…”
Section: Ormentioning
confidence: 99%